Akutni koronarni sindrom - Noč, Marko (Medicinski razgledi, 2002)
This review describes the pathophysiology, pathomorphology and clinical features of acute coronary syndrome. The current approach and treatment of these patients, which begins in the prehospital setting and continues at emergency departments and in hospital coronary care units are also discussed.
Keywords: Angina nestabilna; Myocardial Infarction; Miokardni infarkt; Angina, Unstable; Death, Sudden, Cardiac; Smrt nenadna, srčna; Urgentne, medicinske službe; Emergency Medical Services; Electrocardiography; Elektrokardiografija; Emergency Service, Hospital; Koronarne enote; Coronary Care Units; Urgentna služba bolnišnice; kardiovaskularne bolezni; cardiovascular disease; angina pectoris; urgentna medicina; zdravljenje; therapy